Digital transformation of regional industries through asset modification. Issue 1 (29th July 2020) - Isaksen, Arne; Trippl, Michaela; Kyllingstad, Nina; Rypestøl, Jan Ole
Abstract : Purpose: This paper aims to develop a conceptual framework for analysing wide-ranging digital transformation processes of industries in regional contexts. Design/methodology/approach: The paper includes theoretical work to create a conceptual framework. The paper illustrates and advances the framework by analysing examples from two clusters, one focused on the production of digital products and services and one centred on applying digital tools to make firms' existing activities more efficient. Findings: The paper distinguishes between three main and interlinked categories of digitalisation; development of scientific principles that form the basis for developing digital technologies; making of digital products and services; and application of these in production and work processes. Digital transformation of industries located in particular regions relate to changes of (regional) innovation systems. The authors interpret this as processes of asset modification, distinguishing between re-use of existing assets, creation of new assets and (strategic) destruction of outdated assets. Digital transformation may lead to various forms of innovation and path development activities in regional economies. Practical implications: The paper highlights the importance of modification of assets in organisations and at the level of regional innovation systems to support digitalisation. Organisations need to build absorptive capacity for digitalisation. Regional innovation systems face the challenge to build relevant common assets. Originality/value: The paper advocates a comprehensive framework to better understand how digital transformation unfolds. It challenges established economic geography approaches, which propagate firm-based views and centre stage skill and technological relatedness. An alternative conceptual framework for scrutinising digital transformation processes in industries in regional contexts is presented.